2022
DOI: 10.1161/hypertensionaha.122.19307
|View full text |Cite
|
Sign up to set email alerts
|

Selective IgA Deficiency in Spontaneously Hypertensive Rats With Gut Dysbiosis

Abstract: Background: The spontaneously hypertensive rat (SHR) is extensively used to study hypertension. Gut microbiota dysbiosis is a notable feature in SHR for reasons unknown. Immunoglobulin A (IgA) is a major host factor required for gut microbiota homeostasis. We hypothesized that inadequate IgA contributes to gut microbiota dysbiosis in SHR. methods: IgA was measured in feces, cecum, serum, liver, gut-associated lymphoid tissue, and milk fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“… 18 , 59 Immune responses to serum IgA and secretory IgA are disparate. It was speculated that both renal translocation of secretory IgA-encapsulated bacteria digested by IgA protease found in the present study, and selective deficiency of serum IgA in SHRs reported previously, 58 produce similar consequences during hypertension, but the underlying mechanisms might be quite different. The potential correlations between these findings and hypertension pathogenesis warrant further investigation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“… 18 , 59 Immune responses to serum IgA and secretory IgA are disparate. It was speculated that both renal translocation of secretory IgA-encapsulated bacteria digested by IgA protease found in the present study, and selective deficiency of serum IgA in SHRs reported previously, 58 produce similar consequences during hypertension, but the underlying mechanisms might be quite different. The potential correlations between these findings and hypertension pathogenesis warrant further investigation.…”
Section: Discussionsupporting
confidence: 67%
“… 58 Serum IgA, which can eliminate a large number of antigens, including bacteria and viruses, and maintain the stability of the internal environment without eliciting inflammation, was determined in SHRs with disordered intestinal flora. 58 Here, we mainly focused on the crucial role of secretory IgA in the translocation of gut microbiota to extraintestinal organs, as IgA is known to selectively bind to specific bacterial species and exert important functions during bacterial colonization in the intestinal tract. 18 , 59 Immune responses to serum IgA and secretory IgA are disparate.…”
Section: Discussionmentioning
confidence: 99%
“…It has become a general agreement that there is a tight connection of gut microbiota with blood pressure regulation under the confirmation of many animal models, including spontaneously hypertensive rats (SHR), Ang II–induced hypertensive rats, and Dahl-salt sensitive rats [ 99 , 100 , 101 , 102 , 103 ]. Studies reported that Bifidobacteria could increase the activity of nitric oxide synthase (eNOS) while decreasing the activity of serum catalase [ 104 ].…”
Section: Imbalance Of Gut Microbes and Cvdmentioning
confidence: 99%
“…Specific microbiota, including Romboutsia, Turicibacter, Ileibacterium, and Dubosiella, have affinity to prompt host IgA binding, which may promote the development of hypertension, potentially through the gut-brain axis. [243][244][245] Many of the aforementioned diet-derived and microbemediated metabolites, including TMAO and SCFAs, also play a role in modulating blood pressure. 246 For example, microbe-derived SCFAs bind to olfactory and G-proteincoupled receptors (Olfr78 and Gpr41) in the kidney and vascular endothelium to modulate vasodilation, heart rate, and blood pressure.…”
Section: Effects Of Gut Microbiota On Body Weight Regulation Inflamma...mentioning
confidence: 99%